Low-cost satellite receiver system using RTL-SDR technology for weather monitoring - Mohd Aris, Nor Azlan; Mohamed Yunus, Mawarni; Mohd Zarawi, Muhammad Aiman; Rezuan, Muhammad Faiz Aiman; Shahrulnizam, Afiq; Wan Zaini, Wan Irfan Syahmeey (Research and Scientific Innovation Society, 2025)
This paper presents the development of a low-cost satellite receiver system using RTL-SDR technology for capturing NOAA weather satellite signals. The system integrates a cross-dipole antenna and a Low-Noise Amplifier (LNA) to enhance signal reception in the 137-138 MHz frequency range. Software components include SDR# for signal processing and WXtoImg for image generation from Automatic Picture Transmission (APT) signals. Results demonstrate effective signal reception with high Signal-to-Noise Ratios (SNR) and wide antenna coverage, enabling real-time imaging of weather phenomena. The system demonstrates potential applications in meteorology, disaster management, and climate research, offering accessible tools for real-time weather monitoring and analysis. By addressing the barriers of cost and accessibility, it serves as a model for expanding weather-monitoring capabilities, particularly in regions with limited infrastructure. Future improvements aim to optimize antenna design and software capabilities for broader deployment in remote and underserved areas.